A Nondestructive Testing Research Based on Metal Bumper Bar System Inspired by Guided-wave - Yang Hu; Wang Cheng (Indonesian Journal of Electrical Engineering and Computer Science, 2012)
During the nondestructive testing for metal bumper bar system, it is a critical problem that it cannot identify the reflected wave. Based on the guided-wave inspiration and through studying lots of simulations, this paper systematically analyses the states of quality test for metal bumper bar system in the following four aspects respectively: area inspired by guided-wave, time inspired by guided-wave, head-wave width inspired by guided-wave and rate inspired by guided-wave. The paper also resolves completely the critical problem and completes the subject of quality test. DOI: http://dx.doi.org/10.11591/telkomnika.v10i4.866